Value of Information on Root and Butt Rot Presence When Choosing Tree Species for a Previously Spruce-Dominated Stand in Norway - Aza, Ana; Kangas, Annika; Kallio, Maarit (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Because the two common tree species in Norway, Picea abies L. Karst (Norway spruce) and Pinus sylvestris L. (Scots pine), differ in their susceptibility to the fungus Heterobasidion spp., converting at least parts of the rot-infested spruce stands to pine pays-off economically in some cases. Pixel-level information on rot levels and site indexes (SI) across the stand are required to identify these cases to make decisions that increase the expected economic return of the stand. Applying the Value of Information (VoI) concept, we assessed the value of such information when choosing between planting spruce and pine on a clear-cut spruce stand. The VoIs were highest for the stands of medium–low dominant SI. There, the shift from spruce to pine in some pixels instead of planting spruce across the whole stand has the best-expected impact on the stand’s net present value. Additionally, planting densities are more often adjusted to the pixel SI in these dominant SIs. Given that the stand’s dominant SI is known, information on rot levels alone is more valuable than information on SI alone. The lower the interest rate in decision-making, the more the forest owner is willing to invest in information supporting forest management.
Keywords: tree species selection; root and butt rot uncertainty; site index uncertainty; Norway spruce; Scots pine; value of information